Comparative study of tomato (Solanum lycopersicum L.) culturing under different fertilization schemes - Bustos Barrera, Edgar Esteban; Solís Oba María Myrna; Castro Rivera, Rigoberto; Ocaranza Sánchez Erik; Tapia López Lilia; García Barrera Laura Jeannette; Solís Oba Aida (Revista Mexicana de Ciencias Agrícolas, 2017)
The use of various fertilizers, chemical, organic or biofertilizers has been formulated and reported; however, most producers have focused on the use of agrochemicals, causing environmental problems. The aim of this paper was to evaluate various fertilizers on germination and production of tomato (Solanum lycopersicum L.) and its production cost. Evaluated fertilizers were bioles of anaerobic digestion of cow and pig manures, Azospirillum brasilense, and three commercial products (Regena, Nubiotek and Agromil). The experiment was carried out in 2014 under greenhouse conditions, in Tepetitla de Lardizábal, Tlaxcala. It began from tomato cuttings of three months age, every 10 days each treatment was applied in a foliar way and the irrigation to maintain the humidity of field. The best treatment was obtained with biol obtained from the digestion of cow manure, higher yield and lower production cost were obtained by using it (12.9 kg m2 tomato, 0.60 MN kg respectively); followed by the fertilization system used by the producer (Regena with Nubiotek) which was of 11.98 kg m-2 tomato, with a production cost of 0.64 MN kg. The use of anaerobic digestion has several advantages, it helps to reduce contamination by the inadequate disposal of manures, and allows the obtaining of biogas combustible for the greenhouses heating. The application of simple procedures, such as anaerobic digestion, are economic and environmentally friendly alternatives to treat agricultural residues and obtain products of agronomic interest.